A Review On Electronic Personalized Health Records - Salahuddin, Lizawati; Mohd Yaacob, Noorayisahbe; Abd Ghani, Mohd Khanapi; Abdul Samad, Shibghatullah (Penerbit Universiti, UTeM, 2018)

(untitled)
In accordance with the current information communication technology growth up in widely used at everywhere. Therefore the implementation in ICT is highly assisted patient on their health.As the current technology can be access at everywhere in anytime,the electronic personalized health records are considered as the best solution for the patient to care and monitor their health.This research paper provides a cross review of relevant literature from the previous study in order to clarify the rationality.Its continue with reviewing, comparing and contrasting the existing studies in order to obtain the factors that influence the adoption of electronic personalized health records.A summary that clarifies the relation each factor has been mentioned serve as the foundation for this empirical analysis.In addition,a logical justification is provided concerning the theory based meta-analysis from other studies.